Skin Cancer Risk-Lowering Behaviors and Skincare Habits of Youth Ages 18-25 Years (International Journal of Studies in Nursing, 2018)
Young adults are known for feeling invincible and thus engaging in risky behaviors. One such risky behavior is not protecting themselves from the sun, which can cause skin cancer. The purpose of this study was to determine the skin cancer risk-lowering behaviors and skincare habits among youth ages 18 to 25 years. The findings indicated that a high level of knowledge does not equal regular use of risk-lowering behaviors. This study was quantitative, cross-sectional, and non-experimental. The survey, consisting of 20 Likert-type scale statements, was given in a college consisting of about 2000 students of which 120 college undergraduates participated. Orem’s self-care theory was used as a guide for the study. Participants tended to agree that the use of sunscreen would help protect them from getting skin cancer (M=2.88, SD=0.57), and that sunlight causes skin cancer (M=2.80, SD=0.70). Despite having an adequate level of knowledge on skin cancer risk factors, individuals did not follow through with correct risk-lowering behaviors. For risk-lowering behaviors, more than half of the participants regularly used sunscreen when exposed to the sun (M=2.50, SD=0.90), and most never used tanning beds (M=1.20, SD=0.60).